Managing Stress in the Workplace: A Bibliometric Review of Coping Strategies and Resilience - Putra, Alfa Santoso Budiwidjojo; Sari, Vincentia Indah Puspita (Bulletin of Counseling and Psychotherapy, 2025)
The study aims to conduct a comprehensive bibliometric review of coping strategies and resilience in the context of human resource management (HRM) for managing workplace stress. The focus is on scientific publications from 2019 to 2024 indexed in the Dimensions database. The method used is bibliometric analysis with VOSviewer software to map research trends, identify influential articles and authors, and analyze collaboration and co-citation networks. The results provide a comprehensive map of current trends in workplace stress, coping strategies, and HRM, identifying research gaps and future directions. This study also synthesizes best practices in applying coping strategies and HRM to manage workplace stress. In conclusion, this research provides a strong scientific foundation for developing evidence-based interventions to manage workplace stress and helps organizations create healthier and more productive work environments.